Materialisme Dalam Kajian Ilmu Filsafat - Aisyah, Helda Lara (Yayasan Sembilan Pemuda Indonesia, 2023)
Globalization has a big influence on modern materialism. Living needs are increasing, but income cannot meet them. This is what makes many people take the easy path by making everything legal to fulfill all their wants and needs. This article provides information in the form of a review of materialism in the study of philosophy both in the realms of understanding religion, economics, politics and education. The writing method is carried out by article review. Furthermore, the results obtained show that materialism in religion is motivated by the understanding of God as creator, in economics it shows that economic structure is the basis of every historical movement. The history of fashion is based on the material forces of production and their reciprocal relationships. Then in politics it is proven by a wise attitude full of wisdom in education. Materialization, or the process of making everything materially valuable, has occurred throughout the Indonesian education system.